Re-imagining business ethics meaningful solutions for a global economy - Pava, Moses L.; Primeaux, Patrick (Research in ethical issues in organizations ;, 2002)
Each of the articles in this volume, authored by researchers from around the world, focuses on new and emerging issues in business and organizational ethics. In every case, the authors offer creative insights and new perspectives.